Hypoglycaemic activity of ethanolic extract of Garcinia mangostana Linn. in normoglycaemic and streptozotocin-induced diabetic rats - Bakhtiar, M. Taher; Tengku Zakaria, Tengku Muhamad Faris Syafiq; Darnis, Deny Susanti; Zakaria, Zainul Amiruddin (BioMed Central, 2016)
Background Various parts of Garcinia mangostana Linn., including its pericarp, have been traditionally used to treat a variety of ailments. In an attempt to establish its medicinal value, the present study was carried out to determine the hypoglycaemic potential of G. mangostana pericarp ethanolic extract (GME) using the streptozotocin-induced (STZ) diabetic rats.